1991
DOI: 10.1083/jcb.115.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of synaptophysin with transferrin receptors: implications for synaptic vesicle biogenesis.

Abstract: Abstract. We have reported previously that the synaptic vesicle (SV) protein synaptophysin, when expressed in fibroblastic CHO cells, accumulates in a population of recycling microvesicles . Based on preliminary im munofluorescence observations, we had suggested that synaptophysin is targeted to the preexisting population of microvesicles that recycle transferrin (Johnston, P. A., P. L. Cameron, H. Stukenbrok, R. Jahn, P. De Camilli, and T. C. Siidhof . 1989. EMBO (Eur Mol . Biol. Organ.) J. 8:2863-2872) . In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
221
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(255 citation statements)
references
References 56 publications
30
221
3
Order By: Relevance
“…The two populations are also similar morphologically with multivesicular and tubular domains, although the tubular domain is far more extensive in the somatodendritic region (Parton et al, 1992). The demonstration of differences in sensitivity to BFA, however, suggests that their molecular compositions may be distinct (Cameron et al, 1991). We have now shown that EEA1 is associated exclusively with endosomes of the somatodendritic domains of mature rat hippocampal neurons and not with axonal endosomes marked by internalized antibodies to synaptotagmin.…”
mentioning
confidence: 65%
“…The two populations are also similar morphologically with multivesicular and tubular domains, although the tubular domain is far more extensive in the somatodendritic region (Parton et al, 1992). The demonstration of differences in sensitivity to BFA, however, suggests that their molecular compositions may be distinct (Cameron et al, 1991). We have now shown that EEA1 is associated exclusively with endosomes of the somatodendritic domains of mature rat hippocampal neurons and not with axonal endosomes marked by internalized antibodies to synaptotagmin.…”
mentioning
confidence: 65%
“…Indeed, one recent line of evidence suggests that synaptophysin-positive microvesicles perform exocytotic-endocytotic recycling. Synaptophysin is targeted into a pathway of recycling microvesicles in both neuroendocrine cell line PC12 and synaptophysin-transfected fibroblasts (17), and in PC12 cells synaptophysin is further sorted into specialized vesicle population similar to authentic synaptic vesicles (3,4,20). Synaptophysin-positive microvesicles in pancreatic /3-cell are associated with GABAsynthesizing enzyme and are suggested to store GABA (31).…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol velocity gradients were performed as described (Cameron et al, 1991). Briefly, INS-1E cell supernatants were prepared as described above for sucrose gradients [except that the homogenization buffer was (in mM) 150 NaCl, 10 HEPES, 1 EGTA, 0.1 MgCl 2 , and 1ϫ Complete protease inhibitor (Roche), pH 7.4] and loaded onto a 5-25% continuous glycerol gradient with a 50% sucrose cushion.…”
Section: Expression and Detection Of Clc-3 In Ins-1e Cells And Chromamentioning
confidence: 99%